2003
DOI: 10.1103/physrevb.67.134109
|View full text |Cite
|
Sign up to set email alerts
|

Uniaxial phase transition in Si:Ab initiocalculations

Abstract: Based on a previously proposed thermodynamic analysis [1] , we study the relative stabilities of five Si phases under unaxial compression using ab initio methods. The five phases are diamond, βSn, simple-hexagonal (sh), simple-cubic, and hcp structures.The possible phase-transition patterns were investigated by considering the phase transitions between any two chosen phases of the five phases. By analyzing the different contributions to the relative phase stability, we identified the most important factors in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
4
10
0
Order By: Relevance
“…The good agreement of our results with the ones of Cheng et al 53,54 confirm the reliability of our method, which provides a larger field of applications. In addition, our method can be extended to, e.g., the β-tin→Imma→sh transitions in Si and Ge.…”
Section: Discussion Of the Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The good agreement of our results with the ones of Cheng et al 53,54 confirm the reliability of our method, which provides a larger field of applications. In addition, our method can be extended to, e.g., the β-tin→Imma→sh transitions in Si and Ge.…”
Section: Discussion Of the Resultssupporting
confidence: 90%
“…53,54,74,75,76,77 Directly comparable with our results are just the ones from Lee et al 74 and Cheng et al 53,54 Besides the transition pressures also the function p 53,54 restricted themselves to the enthalpy difference between the phases using path integrals, the enthalpy barrier was not accessible to them.…”
Section: Discussion Of the Resultssupporting
confidence: 90%
“…We observe that ∆E tot is within 0.20-0.45 eV/atom for the sc, sh, and β-tin phases, for both Si and Ge. Our ∆E tot results for the sc, sh, and β-tin phases of Si, and for the β-tin phase of Ge are in good agreement with recent GGA calculations [13,14]. As a further test of the reliability of our calculations, we consider the structural transition from diamond to β-tin, that occurs for both Si and Ge under pressure.…”
supporting
confidence: 86%
“…Nanoindentation studies with various indenter-shapes 2 have shown that non-hydrostatic conditions lower the transformation stress, which is in accordance with theoretical considerations by Gilman (1993a) as well as various atomistic studies (cf. Lee et al, 1997;Cheng et al, 2001;Cheng, 2003;Gaál-Nagy and Strauch, 2006), which suggest a linear relationship between the transformation pressure p and applied von Mises equivalent stress S q := √ 3 /2 S . Transformation events during unloading appear on the force-displacement (P−h) curve (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This choice reproduces the experimentally observed phase transition under hydrostatic compression (Hu et al, 1986), without predicting transformations in hydrostatic tension. Further, the linear relationship between equivalent stress S q and pressure p on the limit surface suggested by MD simulations (Cheng et al, 2001;Cheng, 2003;Gaál-Nagy and Strauch, 2006;Lee et al, 1997) can be smoothly approximated with an arbitrary order of accuracy. The corresponding flow potential is also chosen to be a hyperboloid of revolution, albeit not necessary the same one.…”
Section: Ld-si → Hd-simentioning
confidence: 99%